Production of Lactobionic Acid Using Gold Nanoparticles Synthesized with Fruit Myrciaria dubia Extract - Jeaneth M. Medina-Pérez; Melanie A. Zegarra-Zegarra; José A. Villanueva-Salas; Betty M. Salazar-Pinto; Susan S. Flores-Calla; Angel G. Ramírez-Valverde; Hugo G. Jiménez-Pacheco; Elvis G. Gonzales-Condori (Journal of Nanotechnology)
Lactobionic acid (LBA) is a polyhydroxy acid with attractive properties in the pharmaceutical, cosmetic, food, medical, and chemical industries, making it a versatile product with multiple applications, which supports the various studies aimed at its production by increasingly more simple, efficient, and environmentally friendly processes. For this reason, the purpose of this research was to synthesize gold nanoparticles (AuNPs) by a synthesis process using Myrciaria dubia (Camu camu) fruit extract. Subsequently, AuNPs were used to produce LBA from lactose. The results demonstrate that the Myrciaria dubia extract manages to synthesize AuNPs that were characterized by UV/vis spectrophotometry, energy-dispersive X-ray spectroscopy (EDX), and Zetasizer. LBA was quantified by FTIR-ATR spectroscopy and ion chromatography. The results showed that AuNPs succeeded in producing LBA from lactose showing the highest LBA production efficiency at a dose of 0.5 g/L and a temperature of 60°C. It has been shown that the AuNPs obtained by synthesis using the Myrciaria dubia extract efficiently catalyze the production of LBA from lactose, with a yield of 45.24%, which can be used to produce LBA for industrial or research purposes.